Selected mechanical properties and the structural grading of young Pinus patula sawn timber - Dowse, George Patrick (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Dept. of Forest and Wood Science)--University of Stellenbosch, 2010.